Giving Processed Gonad of Sea Urchins and Skipjack Fish (Katsuwonus pelamis) to Stunted Children: Acceptability and Effectiveness - Hariani Hariani; Teguh Fathurrahman; Wiralis Wiralis; Trina Astuti; Imanuddin Imanuddin (Public Health of Indonesia)
Background:Stuntingis a critical chronic nutritional issue prevalent in developing countries, including Indonesia, with profound effects on children's physical growth, cognitive development, and future productivity.